2019
DOI: 10.1111/tbed.13275
|View full text |Cite
|
Sign up to set email alerts
|

First detection ofMycobacterium bovisinfection in Giraffe (Giraffa camelopardalis) in the Greater Kruger National Park Complex: Role and implications

Abstract: Bovine tuberculosis (bovine TB) caused by Mycobacterium bovis has become endemic in some wildlife populations in South Africa. The disease has been reported in 21 wildlife species in the country. In this study, we report M. bovis infection in two female giraffes (Giraffa camelopardalis) from two different nature reserves within the Greater Kruger National Park Complex (GKNPC). Mycobacterium bovis was isolated from tissue lesions consistent with macroscopic appearance of tuberculosis (TB) and confirmed by polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Bovine tuberculosis (bTB), a chronic granulomatous inflammatory disease is caused mainly by Mycobacterium bovis (M. bovis) [1]. Via the respiratory or digestive tract, M. bovis can infect a wide range of hosts, including many common mammals such as cattle, humans, non-human primates, giraffes, seals, goats, cats, dogs, pigs, buffalo, badgers, possums, deer, and bison [2][3][4], but it also poses a major threat to some endangered species [5]. Before pasteurization of milk, M. bovis was deemed the leading cause of death in children from abdominal tuberculosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bovine tuberculosis (bTB), a chronic granulomatous inflammatory disease is caused mainly by Mycobacterium bovis (M. bovis) [1]. Via the respiratory or digestive tract, M. bovis can infect a wide range of hosts, including many common mammals such as cattle, humans, non-human primates, giraffes, seals, goats, cats, dogs, pigs, buffalo, badgers, possums, deer, and bison [2][3][4], but it also poses a major threat to some endangered species [5]. Before pasteurization of milk, M. bovis was deemed the leading cause of death in children from abdominal tuberculosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…the maintenance and the spill‐over or dead‐end hosts (Ayele et al., 2004 ). In South Africa, bTB is endemic and M. bovis infection has been reported in cattle, pigs and 21 different wildlife species (Hlokwe et al., 2014 , 2019 ; Michel, 2008 ). A recent study by Hlokwe and colleagues ( 2014 ) demonstrated that bTB had not only increased in spatial distribution in South Africa but that the number of wildlife that can be infected by the disease has also increased in comparison to a decade ago (Hlokwe et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, bTB is endemic and M. bovis infection has been reported in cattle, pigs and 21 different wildlife species (Hlokwe et al., 2014 , 2019 ; Michel, 2008 ). A recent study by Hlokwe and colleagues ( 2014 ) demonstrated that bTB had not only increased in spatial distribution in South Africa but that the number of wildlife that can be infected by the disease has also increased in comparison to a decade ago (Hlokwe et al., 2019 ). The prevalence of bTB in commercial cattle herds in South Africa was reduced to 0.4% in 1995 due to implementation of the test and slaughter programme which was introduced in 1969 (Michel, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following the spillover of bTB from cattle to wildlife, African buffalo (Syncerus caffer) emerged as the maintenance host, with far-reaching implications for multispecies ecosystems because infected buffaloes act as a source of M. bovis to any mammalian species sharing the habitat with them (De Vos et al 2001). As a consequence, M. bovis has infected and been diagnosed in 21 wildlife species (Hlokwe et al 2019;Michel et al 2015), including near-threatened, rare and endangered wildlife species such as white and black rhinoceros and wild dog (Higgitt et al 2019;Miller et al 2016Miller et al , 2017bMiller et al , 2018. In addition to buffalo, greater kudu (Tragelaphus strepsiceros) has shown the potential to act as a maintenance host and most probably responsible for introducing M. bovis into a conservation area (Michel et al 2009).…”
Section: Introductionmentioning
confidence: 99%